(untitled) (Medico Legal Update, 2021)
In the current global era, multicultural education is a requisite for those who attain higher education, such as nursing majors working in a community with people from a variety of cultural backgrounds. This study aimed to explore the effect of multicultural education by identifying cultural competency (CC) and multicultural acceptance (MA) among two groups of students and professionals who majored in nursing. A series of surveys was conducted targeting nursing students and clinical professionals. Out of 189 participants, data from 98 participants with experience of multicultural education and 91 participants without experience of multicultural education was analyzed. Independent t-tests, correlation tests, and regression analysis were conducted to examine the effect of multicultural education, and to identify the correlation between CC and MA and the factors influencing them through the comparison of data from each group. The results demonstrated two major points. First, multicultural education was shown to enhance CC and MA of the participants. Second, cultural knowledge and cultural experience were important factors influencing MA. These results can be used to provide educational direction regarding cultural competency and multicultural acceptance, ultimately leading to provision of better healthcare services in multicultural communities.